Isofront in the Eastern Siberian Region (1930s) - Lisitsina, Yana (project baikal, 2019)
The history of the formation of the organization of the Union of Soviet Artists in the remote regions of the country has not been fully studied, but it is of interest for understanding the features of the development of domestic fine art. The article discusses the process of formation of branches of the East Siberian Regional Union of Soviet Artists, which existed for a short period and laid the foundation for separate territorial organizations of Soviet artists. The research is based on the documents deposited in the funds of the State Archive of the Latest History of the Irkutsk Region, which allows us to reconstruct the process of unification of provincial artists into a creative union, which began with the decree of the Central Committee of the All-Union Communist Party of Bolsheviks in 1932.
Keywords: Union of Soviet Artists of the East Siberian Region; Irkutsk artists; Soviet art of the 1930s